Review Image Processing for Mapping in RVP Fixed Wing - Cece Reki; Zahraa Faisal (Tinta Emas Publisher, 2025)
In Indonesia, there is a high demand for land measurement and mapping, especially because many land areas are still unmapped. Remotely Piloted Vehicles (RPVs) of the fixed-wing type are unmanned aircraft technology that can perform flights with automatic or manual control. RPVs have several advantages that make them suitable for land mapping purposes. This technology can be used to map areas with multiple targets, provide flexibility in terms of timing for aerial photography, produce images with detailed spatial resolution, and at a relatively lower cost compared to conventional mapping methods. This research will focus on modifying an RPV by adding a camera for aerial mapping purposes. The stages of this research consist of system analysis and experimental evaluation. The system analysis involves using software called Mission Planner to create waypoint coordinates. The RPV will receive this data to perform automated aerial photography according to the commands given in the Mission Planner software. The experimental evaluation is conducted by processing the captured images or photographs using software such as Agisoft Metashape, which will generate high-accuracy aerial maps.